2008
DOI: 10.3892/or.19.4.1055
|View full text |Cite
|
Sign up to set email alerts
|

Detection of isolated tumour cells in the blood and bone marrow of patients with gastric cancer by combined sorting, isolation and determination of MAGE-1, -2 mRNA expression

Abstract: Abstract. The detection of isolated (circulating or disseminated) tumour cells (ITC) in patients with cancer requires very sensitive methods, as such cells are very rare. In the present study, the method that combines the negative isolation of CD45 -leukocytes from the blood and bone marrow of patients with gastric cancer by flow cytometry, followed by the positive isolation of single cytokeratinpositive (CK + ) cells by a Laser Capture Microdissection System for the determination of MAGE-1, -2 mRNA expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 28 publications
0
6
0
1
Order By: Relevance
“…Total RNA was isolated from the GC1415 tumour cells (1 × 10 6 ) and their TMV using the RNeasy Mini Kit (Qiagen, Hilden, Germany) according to the manufacturer’s protocol. The cDNA synthesis and nested, “real-time” PCR for MAGE-1, -2 and β-actin was performed as previously described [ 16 ]. For the detection of HER-2/neu mRNA “real time” PCR was performed using the following primer pair: for HER-2/neu: sense-5′-CCTCTGACGTCCATCATCTC-3′ and antisense-5′-ATCTTCTCGTGCCGTCGCTT-3′.…”
Section: Methodsmentioning
confidence: 99%
“…Total RNA was isolated from the GC1415 tumour cells (1 × 10 6 ) and their TMV using the RNeasy Mini Kit (Qiagen, Hilden, Germany) according to the manufacturer’s protocol. The cDNA synthesis and nested, “real-time” PCR for MAGE-1, -2 and β-actin was performed as previously described [ 16 ]. For the detection of HER-2/neu mRNA “real time” PCR was performed using the following primer pair: for HER-2/neu: sense-5′-CCTCTGACGTCCATCATCTC-3′ and antisense-5′-ATCTTCTCGTGCCGTCGCTT-3′.…”
Section: Methodsmentioning
confidence: 99%
“…Though the hTERT mRNA might be expressed in the cells of the CRC culture (15), its expression could differentiate human cancer cells from mouse fibroblast J2 cells. The results regarding MAGE mRNA revealed that this gene is a cancer specific oncogene (17,29).…”
Section: Discussionmentioning
confidence: 97%
“…The isolation of total RNA and qPCR for MAGE-1, −2 and β-actin was performed as previously described ( 13 ). For detection of HER-2/neu mRNA qPCR was performed using the following primers: Sense-5′-CCTCTGACGTCCATCATCTC-3′ and antisense-5′-ATCTTCTCGTGCCGTCGCTT-3′.…”
Section: Methodsmentioning
confidence: 99%